Duplex stainless steel fabricated by selective laser melting - Microstructural and mechanical properties - Hengsbach, Florian; Koppa, Peter; Duschik, Kristina; Holzweissig, Martin Joachim; Burns, Madison; Nellesen, Jens; Tillmann, Wolfgang; Tröster, Thomas; Hoyer, Kay-Peter; Schaper, Mirko (Materials & Design)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Structure of counterflow flame of ultrahigh-molecular-weight polyethylene with and without triphenylphosphate - Korobeinichev, O.P.; Gonchikzhapov, M.B.; Paletsky, A.A.; Tereshchenko, A.G.; Shmakov, A.G.; Gerasimov, I.E.; Knyazkov, D.A. (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Structure of Ultrahigh Molecular Weight Polyethylene-Air Counterflow Flame (Физика горения и взрыва)
Keywords: Process Chemistry and Technology; Mechanical Engineering

Mechanical properties of an innovative shear-clinching technology for ultra-high-strength steel and aluminium in lightweight car body structures - Hörhold, Réjane; Müller, Martin; Merklein, Marion; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Investigation on joint characteristics of laser beam welded press hardenable ultra-high strength steels with ferritic-martensitic and martensitic microstructure - Janzen, V.; Meschut, G.; Dahmen, M.; Poprawe, R.; Lindner, S.; Wagener, R.; Melz, T. (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Development of a Testing Method for the Identification of Friction Coefficients for Numerical Modeling of the Shear-Clinching Process - Müller, Martin; Vierzigmann, Ulrich; Hörhold, Réjane; Meschut, Gerson; Merklein, Marion (Key Engineering Materials)
Global competition as well as social and scientific megatrends strongly influence the modern car manufacturing industry. One of the most important approaches is the implementation of lightweight constructions. Therefore, the usage of high performance materials with tailored properties gains importance. For safety-relevant components such as automotive passenger cells it is necessary to minimize deformation to reduce the risk of injury for the vehicle occupants during a car accident. Thus, hot stamped high-strength steels have been established. High-strength and low formability of this kind of materials represent new challenges for joining technologies. One possibility to join high-strength steels is the newly developed shear-clinching technology. Due to the use of a combined cutting and joining process, the connection of dissimilar materials with high difference in strength and formability can be achieved. Further research to ensure process reliability and to improve the strength of the joint is required. One possible approach for this is the numerical investigation of the material flow during the joining process. Therefore, the definition of process parameters for the finite element model is necessary. A big impact on the quality of the results has the accuracy of the used friction values. As established testing methods are not suitable for modeling the rather complex tribological system between the joining partners of the shear-clinching process, an innovative testing method is needed. Studies in the field of sheet-bulk metal forming already demonstrated the applicability of the ring compression test for sheet metals. This paper presents a concept for the adaption of the ring compression test to the specific needs of the investigated shear-clinching process. The numerical identification of the friction coefficients is validated by experimental data and first results are qualified by experimental and simulative shear-clinching joints.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Columnar molecular aggregation in the aqueous solutions of disodium cromoglycate - Agra-Kooijman, Dena M.; Singh, Gautam; Lorenz, Alexander; Collings, Peter J.; Kitzerow, Heinz-Siegfried; Kumar, Satyendra (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Planar anchoring strength and pitch measurements in achiral and chiral chromonic liquid crystals using 90-degree twist cells - McGinn, Christine K.; Laderman, Laura I.; Zimmermann, Natalie; Kitzerow, Heinz-Siegfried; Collings, Peter J. (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

The use of radiation-cured adhesives on adhesive stud assembly process - Meschut, Gerson; Süllentrop, Sebastian (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Innovative and Highly Productive Joining Technologies for Multi-Material Lightweight Car Body Structures - Meschut, G.; Janzen, V.; Olfermann, T. (Journal of Materials Engineering and Performance)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Basic Investigations of Non-Pre-Punched Joining by Forming of Aluminium Alloy and High Strength Steel with Shear-Clinching Technology - Merklein, Marion; Meschut, Gerson; Müller, Martin; Hörhold, Réjane (Key Engineering Materials)
Facing a decreasing amount of resources on the one hand and an increasing demand for comfort on the other, more and more attention is being paid to sustainability and care for the environment. Particularly in the automotive sector, lightweight design principles continue to prosper rapidly. As a result, adjusted materials for different applications were developed. Due to the formation of intermetallic phases, most multi-material mixes cannot be welded and require adapted joining technologies. Mechanical joining technologies such as self-piercing riveting and mechanical clinching have proven effective methods of joining lightweight materials like aluminium and ductile steels. New high-strength steels are increasingly used in crash-sections, where limited deformation under impact load is required. These hot stamped steels have a very low elongation at break and therefore a low formability. Currently there is no joining by forming technology without pre-punching available using these grades of steels on die-side. The newly developed shear-clinching process is one possible method of joining this kind of material without additional elements. The fundamental idea of shear-clinching is a single-stage process in which pre-punching of the die-side material is performed by indirect shear-cutting and subsequent forming of the upper layer into this hole. This would immensely enlarge the application segment of mechanical clinching even if hot stamped steels are positioned on die-side. Fundamental studies are required to ensure process reliability and it is necessary to break down the joining process into fragments, like pre-punching and clinching with pre-punched sheet, and superpose them to form the combined procedure shear-clinching. This paper presents a detailed investigation of the sub-process clinching with pre-hole.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Innovative joining technologies for multi-material structures - Meschut, G.; Hahn, O.; Janzen, V.; Olfermann, T. (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Korrosionsverhalten binärer Magnesium-Zink-Legierungen in salzhaltigen Medien - Hoyer, Kay-Peter; Angrisani, Gian Luigi; Klose, Christian; Bach, Friedrich-Wilhelm; Hassel, Thomas (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Weyl asymptotics: From closed to open systems - Potzuweit, A.; Weich, Tobias; Barkhofen, Sonja; Kuhl, U.; Stöckmann, H.-J.; Zworski, M. (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Reduction of flammability of ultrahigh-molecular-weight polyethylene by using triphenyl phosphate additives - Korobeinichev, O.P.; Paletsky, A.A.; Kuibida, L.V.; Gonchikzhapov, M.B.; Shundrina, I.K. (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Doping the nematic liquid crystal 5CB with milled BaTiO3nanoparticles - Lorenz, Alexander; Zimmermann, Natalie; Kumar, Satyendra; Evans, Dean R.; Cook, Gary; Kitzerow, Heinz-Siegfried (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Surface tension and its role for vertical wet etching of silicon - Brockmeier, A; Rodriguez, F J Santos; Harrison, M; Hilleringmann, Ulrich (Journal of Micromechanics and Microengineering)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; Electronic; Optical and Magnetic Materials

Surface tension and its role for vertical wet etching of silicon - Brockmeier, A; Rodriguez, F J Santos; Harrison, M; Hilleringmann, Ulrich (Journal of Micromechanics and Microengineering)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; Electronic; Optical and Magnetic Materials

Einfluss der Oberflächenbehandlung auf das Korrosionsverhalten von Magnesiumlegierungen - Hoyer, Kay-Peter; Hassel, Thomas; Bach, Friedrich-Wilhelm (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Synthesis of highly stable magnesium fluoride suspensions and their application in the corrosion protection of a Magnesium alloy - Waltz, Florian; Swider, Mark A.; Hoyer, Kay-Peter; Hassel, Thomas; Erne, Martin; Möhwald, Kai; Adlung, Matthias; Feldhoff, Armin; Wickleder, Claudia; Bach, Friedrich-Wilhelm; Behrens, Peter (Journal of Materials Science)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

A Newton-Multigrid algrithm for elasto-plastic/viscoplastic problems - Mahnken, Rolf (Computational Mechanics)
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

Dichroic photo- and electroluminescence of oligo p-(phenylene vinylene) derivatives - Lauhof, Marcus W.; Benning, Stephan A.; Kitzerow, Heinz-Siegfried; Vill, Volkmar; Scheliga, Felix; Thorn-Csányi, Emma (Synthetic Metals)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Spin-electronic devices with half-metallic Heusler alloys - Hütten, A.; Schmalhorst, J.; Thomas, A.; Kämmerer, S.; Sacher, Marc; Ebke, D.; Liu, N.-N.; Kou, X.; Reiss, G. (Journal of Alloys and Compounds)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Degradation of organic field-effect transistors made of pentacene - Pannemann, Ch.; Diekmann, T.; Hilleringmann, Ulrich (Journal of Materials Research)
This article reports degradation experiments on organic thin film transistors using the small organic molecule pentacene as the semiconducting material. Starting with degradation inert p -type silicon wafers as the substrate and SiO 2 as the gate dielectric, we show the influence of temperature and exposure to ambient air on the charge carrier field-effect mobility, on-off-ratio, and threshold-voltage. The devices were found to have unambiguously degraded over 3 orders of magnitude in maximum on-current and charge carrier field-effect mobility, but they still operated after a period of 9 months in ambient air conditions. A thermal treatment was carried out in vacuum conditions and revealed a degradation of the charge carrier field-effect mobility, maximum on-current, and threshold voltage.
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Degradation of organic field-effect transistors made of pentacene - Pannemann, Ch.; Diekmann, T.; Hilleringmann, Ulrich (Journal of Materials Research)
This article reports degradation experiments on organic thin film transistors using the small organic molecule pentacene as the semiconducting material. Starting with degradation inert p -type silicon wafers as the substrate and SiO 2 as the gate dielectric, we show the influence of temperature and exposure to ambient air on the charge carrier field-effect mobility, on-off-ratio, and threshold-voltage. The devices were found to have unambiguously degraded over 3 orders of magnitude in maximum on-current and charge carrier field-effect mobility, but they still operated after a period of 9 months in ambient air conditions. A thermal treatment was carried out in vacuum conditions and revealed a degradation of the charge carrier field-effect mobility, maximum on-current, and threshold voltage.
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Director reorientation of a side-chain liquid crystalline polymer under extensional flow - Cormier, Ryan J.; Schmidt, Claudia; Callaghan, Paul T. (Journal of Rheology)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Morphology and fluorescence quenching in photovoltaic samples containing fullerene and poly(p-phenylene-vinylene) derivatives - Röder, T; Kitzerow, Heinz-Siegfried; Hummelen, J.C (Synthetic Metals)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Structures with a minimum feature size of less than 100 nm in CVD-diamond for sensor applications - Otterbach, R.; Hilleringmann, Ulrich; Horstmann, T.J.; Goser, K. (Diamond and Related Materials)
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Mechanical Engineering; General Chemistry; Electronic; Optical and Magnetic Materials

Reactive ion etching of CVD-diamond for piezoresistive pressure sensors - Otterbach, R.; Hilleringmann, Ulrich (Diamond and Related Materials)
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Mechanical Engineering; General Chemistry; Electronic; Optical and Magnetic Materials

Strength difference in compression and tension and pressure dependence of yielding in elasto-plasticity - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Finite element simulation for rock salt with dilatancy boundary coupled to fluid permeation - Mahnken, Rolf; Kohlmeier, M. (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Implicit integration scheme and its consistent linearization for an elastoplastic-damage model with application to concrete - Mahnken, Rolf; Tikhomirov, D.; Stein, E. (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering

Numerical simulation of interface debonding with a combined damage/friction constitutive model - Döbert, C.; Mahnken, Rolf; Stein, E. (Computational Mechanics)
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

A comprehensive study of a multiplicative elastoplasticity model coupled to damage including parameter identification - Mahnken, Rolf (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering

Parameter identification of gradient enhanced damage models with the finite element method - Mahnken, Rolf; Kuhl, Ellen (European Journal of Mechanics - A/Solids)
Keywords: General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; General Materials Science

A unified approach for parameter identification of inelastic material models in the frame of the finite element method - Mahnken, Rolf; Stein, Erwin (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Parameter identification for viscoplastic models based on analytical derivatives of a least-squares functional and stability investigations - Mahnken, Rolf; Stein, Erwin (International Journal of Plasticity)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Parameter identification for finite deformation elasto-plasticity in principal directions - Mahnken, Rolf; Stein, Erwin (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Aspects on the finite-element implementation of the Gurson model including parameter identification - Mahnken, Rolf (International Journal of Plasticity)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Rheology and nuclear magnetic resonance measurements under shear of sodium dodecyl sulfate/decanol/water nematics - Thiele, Thomas; Berret, J.-F.; Müller, Stefan; Schmidt, Claudia (Journal of Rheology)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science